Molinostrongylus longmenensis n. sp. (Strongylida: Molineidae) in the bat Scotophilus kuhlii (Leach; Chiroptera: Vespertilionidae) from China - Ju, Hui-Dong; Jian, Rui; Wang, Shi-Yue; Qin, Li-Yun; Gao, Wei-Li; Xu, Zhen; Zhang, Hong (Frontiers in Veterinary Science, 2024)
A new species of nematode, Molinostrongylus longmenensis n.sp., parasite of the genus Molinostrongylus, is described based on specimens recovered from the small intestine of Scotophilus kuhlii Leach, 1822 (Chiroptera: Vespertilionidae) in Longmen County, Guangdong Province, China. To date, 135 species of bat-parasitic nematodes have been reported worldwide. Overall, 13 species belonging to seven genera in three families have been described in China. The new species is characterized by the presence of three ventral and three dorsal longitudinal cuticular ridges perpendicular to the body surface, which appear posterior to the cephalic vesicle and extend to the caudal bursa in males and the posterior end in females. The female tail has two medium-sized subventral conical processes of equal length, as well as one large dorsal conical process, and one thin spine, lateral alae that extend to the position of the vulva, with a fin-like ending. In addition, the new species was also characterized using molecular approaches, such as sequencing and analyzing the internal transcribed spacer 1 (ITS-1) of the ribosomal DNA.